2012
DOI: 10.7314/apjcp.2012.13.9.4631
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Control Law Enforcement and Compliance in Odisha, India - Implications for Tobacco Control Policy and Practice

Abstract: Introduction: Tobacco use is a leading cause of deaths and disabilities in India, killing about 1.2 lakh people in 2010. About 29% of adults use tobacco on a daily basis and an additional 5% use it occasionally. In Odisha, non-smoking forms are more prevalent than smoking forms. The habit has very high opportunity cost as it reduces the capacity to seek better nutrition, medical care and education. In line with the WHO Framework Convention on Tobacco Control (FCTC), the Cigarettes and Other Tobacco Products Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…Tobacco control measures continue to face many implementation and knowledge dissemination challenges, despite policy achievements since the passage of the Cigarettes and Other Tobacco Products Act (COTPA) (Kaur and Jain, 2012;Panda et al, 2012). While smoking may represent a more "westernized" phenomena, the history and cultural rooting of smokeless tobacco presents a different set of challenges in India's tobacco control measures (Stigler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco control measures continue to face many implementation and knowledge dissemination challenges, despite policy achievements since the passage of the Cigarettes and Other Tobacco Products Act (COTPA) (Kaur and Jain, 2012;Panda et al, 2012). While smoking may represent a more "westernized" phenomena, the history and cultural rooting of smokeless tobacco presents a different set of challenges in India's tobacco control measures (Stigler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Every year more than 8 lakh people die due to tobacco-related diseases. 2 It has also been reported that more than 39% of tobacco users initiated the tobacco habit before the age of 17 years when they were far too young to either resist peer pressure or understand the risks of tobacco use. 3 The Cigarettes and Other Tobacco Products Act (COTPA) (prohibition of advertisement and regulation of trade and commerce, production, supply and distribution) was enacted by the Government of India in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The death toll from tobacco is expected to increase to eight million a year by 2030. 1 The Global Youth Tobacco Survey (GYTS) 2 indicates that 14.6% children in the age group of 13 to 15 years and 34.6% of Indians aged 15 years and above use tobacco in some form or the other. Every year more than 8 lakh people die due to tobacco-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies had been conducted in several countries which focused on the implication of the SFL compliance among the public (Panda et al, 2012;Abidin et al, 2013;Oh et al, 2013). The environmental assessments on the measurement of particulate matter (PM2.5) and air nicotine in public places demonstrated that the concentration of contaminants continues to be high including in spaces where smoking is prohibited by law (King et al, 2011;Abidin et al, 2013;Oh et al, 2013).This evidence showed that non-smoking population continually to be exposed to SHS even in the wake of the SFL implementation.…”
Section: Introductionmentioning
confidence: 99%
“…As a signatory to the treaty, Malaysia and other various countries had developed and implemented smoke-free legislation or SFL that prohibit smoking in public places in order to provide a smoke-free environment to citizens (Kashiwabara et al, 2011;Panda et al, 2012;Abidin et al, 2013;Oh et al, 2013). Malaysia has implemented a partial-SFL which prohibits smoking in 21 types of public spaces (Malaysia Act, 2008;Abidin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%